PENGARUH ORGANIZATIONAL CITIZENSHIP BEHAVIOR TERHADAP KINERJA GURU DI SMAS NURUL ISLAM INDONESIA MEDAN - Rahma Aulia Ashari; Khairuddin Lubis; Abdul Halim (STKIP Subang, 2026)
Organizational Citizenship Behavior can increase the stability of organizational performance. Conscientious employees tend to maintain consistently high-performance levels, thereby reducing variability in work unit performance. However, improving human performance is one of the toughest challenges in the world, namely changing the way other people think. Leaders can change the way they think or perform if they can change the way other people think. In this case, OCB is needed to improve employee performance. The title that the researcher adopted in this research is